THE VALIDITY OF THE COVID-19 FATWA IN REVIEW OF THE AD-DHARAR YUZALU RULES - Achmad Musyahid Idrus (Al-Risalah, 2021)
The covid 19 is a fiqh law product that has been issued by a fatwa institution that competent in Indonesia, which is the Indonesian Ulama Council. It has issued no less than 14 legal fatwas relating to covid 19. Those are the Conduct of Worship in Situations the covid 19 Outbreak, Concerning Guidelines for Prayers for Health Workers who Wear Personal Protective eqiument (APD), Guidelines for the management of Bodies Infected Muslim wirh covid 19, Regarding Utilizatiom Zakat, Infaq and Shadaqah Assets for Covid 19 Outbreak, Guidlines for Takbir Kaifiyyat and Eid al-Fitr Prayers during the Covid 19 pandemic, on organization Friday prayers and jamaahs to prevent covid 19 transmission, on Eid al-Adha prayers and jamaahs to prevent covid 19 transmisssion, on Eid al-Adha prayers and sacrificial animal slaughter the Covid 19 outbreak. The ad-Dharar Yuzalu rule is one of the principles of figh which aims to introduce how imprtant it is to protect lives and descendants from the dangers threats of Covid 19. It’s a virus that can actually threaten lives and offspring, so by using this ad-dharar yuzalu rule, the the main purpose of religion can be realized in human life.